First Observations of the New MEXART's Digital System. Issue 1 (4th January 2022) - Gonzalez‐Esparza, J. A.; Mejia‐Ambriz, J. C.; Aguilar‐Rodriguez, E.; Villanueva, P.; Andrade, E.; Magro, A.; Chiello, R.; Cutajar, D.; Borg, J.; Zarb‐Adami, K.
Abstract: The Mexican Array Radio Telescope (MEXART) is a transit instrument mainly dedicated to performing interplanetary scintillation (IPS) observations with a central operating frequency of 139.65 MHz. The main scientific objective is to perform studies of solar wind properties and space weather effects. MEXART initially operated with an analog beam former (16 × 16 Butler matrix), which produced 16 fixed latitudinal beams. MEXART began operations and reported the first measurements of IPS sources. MEXART's beam forming system had several problems, however. The North‐South beams had poor directivity, with large side lobes, and the instrument did not achieve the expected performance. Therefore, we commissioned the design and construction of a digital back‐end. The digital system solved the problems with the beam forming, increases the bandwidth, and significantly improves the instrument's sensitivity. In this paper, we present the first light of MEXART's digital system. We describe the new technical capabilities of the instrument, and we show some preliminary results: an estimation of the radio telescope's sensitivity (Δ S min = 2.28 ± 0.23 Jy), the transit of the Galaxy at 140 MHz with the simultaneous tracking of 62 latitudinal beams, and an example of an IPS observation and the single‐station methodology for calculating the solar wind speed. The new technical capabilities of the radio telescope will provide the potential for participating in several scientific studies. These include solar wind properties, space weather forecasting, ionospheric perturbations, and astrophysical aims such as the monitoring of repeating fast radio bursts and pulsars' observations. Key Points: Radio telescope dedicated to the study of solar wind properties and space weather effects using the interplanetary scintillation technique The new digital backend has several beamforming configurations, increases the bandwidth, and improves the instrument's sensitivity With the new technical capabilities, the instrument can participate in space weather forecasting and other astrophysical studies